Genome-wide identification and expression analysis of MADS-box transcription factors reveal their involvement in sex determination of hardy rubber tree (Eucommia ulmoides oliv.) - Zhang, Xianzhi; Wang, Xinyi; Pan, Linsi; Guo, Wei; Li, Yongquan; Wang, Wencai (Frontiers in Genetics, 2023)
Eucommia ulmoides is a famous rubber-producing and medicinal tree species that produces unisexual flowers on separate individuals from the earliest stage of stamen/pistil primordium formation. To explore the genetic regulation pathway of sex in E. ulmoides, comprehensive genome-wide analyses and tissue-/sex-specific transcriptome comparisons of MADS-box transcription factors were performed for the first time in this work. Quantitative real-time PCR technique was employed to further validate the expression of genes that are assigned to floral organ ABCDE model. A total of 66 non-redundant E. ulmoides MADS-box (EuMADS) genes were identified, they were classified into Type I (M-type, 17 genes) and Type II (MIKC, 49 genes). Complex protein-motif composition, exon-intron structure and phytohormone-response cis-elements were detected in MIKC-EuMADS genes. Furthermore, 24 differentially-expressed EuMADS genes (DEGs) between male and female flowers, and two DEGs between male and female leaves were revealed. Amongst the 14 floral organ ABCDE model-related genes, there were 6 (A/B/C/E-class) and 5 (A/D/E-class) genes displayed male- and female-biased expression respectively. In particular, one B-class gene EuMADS39 and one A-class gene EuMADS65 were almost exclusively expressed in male trees, no matter in flower or leaf tissues. Collectively, these results suggested a critical role of MADS-box transcription factors in sex determination of E. ulmoides, which is conducive to decoding the molecular regulation mechanism of sex in E. ulmoides.